The Balkan Wars – victory and defeat for Bulgaria (1912-1913) - Хаков, Дженгиз (Balcanica Posnaniensia. Acta et studia, 2012)
After declaring its independence in 1908, in the name of the unification of all Bulgarians in one state Bulgaria carried out a policy of expanding its territory at the expense of the Ottoman provinces in the Balkans. The same policy was followed by all the other Balkan states. In the spring of 1912 under Russian auspices was formed the Balkan Alliance in which took part Bulgaria, Serbia, Greece and Montenegro. In the course of one year two wars with opposite goals and objectives were waged in the Balkans. The first war was between the states from the Balkan Alliance and Turkey, and the second – between Bulgaria and its allies from the Balkan Alliance. The Balkan wars changed radically the map of the Balkans. The Balkan Alliance disintegrated, the contradictions among the Balkan states aggravated and that again set them against each other in the First World War.